2015
DOI: 10.1186/s12889-015-1447-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sitting time and physical activity: interactive associations with mental well-being and productivity in office employees

Abstract: BackgroundLittle is known about how sitting time, alone or in combination with markers of physical activity (PA), influences mental well-being and work productivity. Given the need to develop workplace PA interventions that target employees’ health related efficiency outcomes; this study examined the associations between self-reported sitting time, PA, mental well-being and work productivity in office employees.MethodsDescriptive cross-sectional study. Spanish university office employees (n = 557) completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 38 publications
(41 reference statements)
6
64
1
1
Order By: Relevance
“…Higher presenteeism has been associated with (i) high sitting times before/after work and during lunch hours [26], and (ii) high occupational and total sitting time on workdays in highly active office employees [27]; suggesting that workplace strategies to improve the productivity of office employees should focus on reducing sitting time alongside efforts to increase PA [27]. Given the need to target specific employee behaviors that improve both health and efficiency-related outcomes; understanding whether workplace interventions for reducing occupational sitting promote productivity is a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…Higher presenteeism has been associated with (i) high sitting times before/after work and during lunch hours [26], and (ii) high occupational and total sitting time on workdays in highly active office employees [27]; suggesting that workplace strategies to improve the productivity of office employees should focus on reducing sitting time alongside efforts to increase PA [27]. Given the need to target specific employee behaviors that improve both health and efficiency-related outcomes; understanding whether workplace interventions for reducing occupational sitting promote productivity is a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective well-being is being increasingly seen as an indicator of societal progress (Stiglitz, 2009) and research has demonstrated the importance of positive wellbeing in predicting various health outcomes, including survival independently of negative states such as depression (Pressman & Cohen, 2005). There is limited evidence in relation to sedentary behavior, although recent data has suggested an association between greater work place sitting and lower mental wellbeing in office employees (Puig-Ribera et al, 2015). These analyses were not adjusted for measures of negative affect, such as depressive symptoms, thus results might simply reflect the absence of negative states.…”
Section: Introductionmentioning
confidence: 99%
“…30 For some groups, strategies that focus on improvements in these behaviours simultaneously are effective. 31 Nevertheless, research surrounding effective intervention and policy to achieve this end is not well developed. 3,32 The latest evidence indicates that interventions aiming to increase MVPA, or combine increases in MVPA with reductions in sedentary behaviour are not effective for reducing sedentary time.…”
mentioning
confidence: 99%